Can mastery and performance goals predict learning flow among secondary school students? - Syed Mustafa, Sharifah Muzlia; Elias, Habibah; Roslan, Samsilah; Mohd Noah, Sidek (Center for Promoting Ideas, 2011)
This study investigated the ability of a motivation construct, learning goals to predict flow among high school students. Learning goals and their influences on learning and performance have been researched extensively, but how much can both mastery and performance goals predict students’ engagement in general learning activities is still not well documented. A total of 94 high school students aged sixteen were given questionnaires that measure their experience of flow as well as learning goals as they engage in learning activities in preparation for a major examination. Standard multiple regression analysis found the model (mastery and performance goals) explains 51% of the variance in flow. Further analysis found that of the two goals, mastery goal makes the strongest significant contribution to explaining flow, whereas performance goal was not a significant predictor of flow. The results are discussed in terms of promoting mastery goal as the main ingredient for students to become engage in their learning tasks. Nevertheless, the beneficial role of performance goal is still not rejected.